Regresi Logistik Bootstrap untuk Menentukan Faktor yang Mempengaruhi Tingkat Kemampuan Wirausaha - Muhammad Ridho; Dodi Devianto (Jurnal Matematika MANTIK, 2019)
The purpose of this study is to determine the factors that affect the level of entrepreneurial capability in tourism of rural area in Nagari Salayo of West Sumatra. The level of entrepreneurial capability is the response variable in this study with an ordinal scale consisting of four categories, they are lower, middle, high, or very high. Whereas the predictor variables consist of 4 socio-demographic factor variables, they are gender, education level, age group and occupation, and also 5 entrepreneurial motivation variables. To determine the predictor variables that are significantly affecting response variables, an ordinal logistic regression with a bootstrap estimation is executed. The study’s result shows two predictor variables that affect the response variable significantly, they are the entrepreneurial motive and social motive with the hit ratio of 61,667%. With that result, the model formed by bootstrapping logistic regression is able to determine the level of entrepreneurial capability in tourism of the rural area.